PENGARUH DISIPLIN KERJA, KOMPETENSI, SERTA KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PT. SUCOFINDO (PERSERO) CABANG PALEMBANG - Fitriani Ariko, Meilinda (Universitas muhammadiyah palembang, 2018)
This research aims to find impact of work discipline, competence, occupational health and safety to employees performance on Sucofindo, Co. Ltd Branch Palembang. Design used in this research is associative. Variables used are four variables, those are independent variables which Work Discipline (X1), Competence (X2), and Occupational Health and Safety (X3), and also dependent variables is Employees Performance (Y). Population in this research as much 135 persons. Sampling technique useed probability sampling, sampling method used cluster sampling. Sample used as much as 101 persons. The analytical tool used is multiple linear regression.According to the research result, find: (1) Work discipline, competence, occupational health and safety simultaneously have positive and significant effects to employees performance on on Sucofindo, Co. Ltd Branch Palembang, (2) Work discipline and competence partially have positive and significant effects to employees performance on on Sucofindo, Co. Ltd Branch Palembang, and (3) Occupational health and safety have no significant effects to employees performance on on Sucofindo, Co. Ltd Branch Palembang.